Anomalous Terahertz Reflection and Scattering by Flexible and Conformal Coding Metamaterials. Issue 10 (30th June 2015) - Liang, Lanju; Qi, Meiqing; Yang, Jing; Shen, Xiaopeng; Zhai, Jiquan; Xu, Weizong; Jin, Biaobing; Liu, Weiwei; Feng, Yijun; Zhang, Caihong; Lu, Hai; Chen, Hou‐Tong; et al.
<x xml:space="preserve">Abstract</x> Arbitrary control of terahertz (THz) waves remains a significant challenge although it promises many important applications. Here, a method to tailor the reflection and scattering of THz waves in an anomalous manner by using 1‐bit coding metamaterials is presented. Specific coding sequences result in various THz far‐field reflection and scattering patterns, ranging from a single beam to two, three, and numerous beams, which depart obviously from the ordinary Snell's law of reflection. By optimizing the coding sequences, a wideband THz thin film metamaterial with extremely low specular reflection, due to the scattering of the incident wave into various directions, is demonstrated. As a result, the reflection from a flat and flexible metamaterial can be nearly uniformly distributed in the half space with small intensity at each specific direction, manifesting a diffuse reflection from a rough surface. Both simulation and experimental results show that a reflectivity less than −10 dB is achieved over a wide frequency range from 0.8 to 1.4 THz, and it is insensitive to the polarization of the incident wave. This work reveals new opportunities arising from coding metamaterials in effective manipulation of THz wave propagation and may offer widespread applications.